Experimental and numerical investigations of the dynamic responses of low and medium speed maglev train-track-bridge coupled system. Issue 5 (4th May 2022) - Li, Miao; Luo, Shihui; Ma, Weihua; Li, Tie; Gao, Dinggang; Xu, Ziqiang
Abstract : In recent years, low and medium speed maglev (LMSM) transportation system has been greatly promoted in China to meet different social demands. Accordingly, a LMSM train using levitation frames with mid-set air springs has been developed, and it is necessary to investigate the dynamic characteristics of its train-track-bridge coupled system. First, environmental vibration tests were conducted on the bridge to study its self-vibration characteristics. Then, field tests were carried out on this coupled system within the 60 km/h speed range. Subsequently, a three-dimensional rigid-flexible coupled dynamics model of the system was developed to evaluate its dynamic behavior at higher speeds. Results show that the first-order vertical and lateral bending frequencies of the bridge are 7.32 Hz and 6.00 Hz, respectively; train speed has little effect on the vertical dynamic displacement of the track-bridge system, yet has a significant impact on the acceleration responses of the coupled system; key dynamic indicators of the bridge meet the relevant requirements; the vertical ride quality of car body is not so good as that in the lateral direction, but on the whole the train has "Good" ride quality. These results can provide a useful reference for the optimal design of LMSM transportation systems.